PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT.ASERA TIRTA POSIDONIA KOTA PALOPO - Fika Pramulya; Mayasari; Anastasya Palinggi; Nirmal; Ishak Runi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is about the Influence of Organizational Culture on Employee Performance at PT. Asera Tirta Posidonia Palopo. A strong culture is related to high employee performance in the organization. A strong culture must be emphasized and taught to old and new employees, employees do not consciously have the value of a strong culture. With this, it is possible to create uniform actions and effective communication in the organization. The relationship between personnel in an organization is something that needs to be paid attention to whether or not an organization is successful in achieving its goals, a harmonious relationship between personnel and each individual's awareness of their rights, obligations and responsibilities. Having an organizational culture can help a company achieve its goals effectively and efficiently. This is in accordance with the aim of organizational culture, namely creating a harmonious environment and relationships between employees which will have an impact on achieving maximum company targets or goals. Data collection is carried out through qualitative methods, namely by distributing questionnaires to employees. The results can be concluded that organizational culture influences employee performance, which shows that the organizational culture of PT Asera Tirta Posidonia, Palopo City, both in concept and in its application, work discipline is also one